Tindak Tutur Ilokusi dalam Film Pendek Episode Warga Baru Kampung Pojok di Kanal YouTube Dika BJ - Miftahul Jannah; Hosniyeh Hosniyeh (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research is motivated by the importance of pragmatic studies in understanding language use as a form of social action, particularly illocutionary speech acts in YouTube-based digital media that represent everyday social life. The study aims to describe the forms and functions of illocutionary speech acts used in the short film episode “Warga Baru Kampung Pojok” on the Dika BJ YouTube channel, as well as to reveal how these utterances reflect the social and cultural realities of Javanese society. The research problem focuses on identifying the types of illocutionary speech acts found in the short film “Warga Baru Kampung Pojok.” This study employs a descriptive qualitative method with a pragmatic approach, using John Searle’s speech act theory as the analytical framework. The research subject consists of the utterances produced by the characters in the short film “Warga Baru Kampung Pojok” uploaded on the Dika BJ YouTube channel. Data were collected through observation and note-taking techniques and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that 44 illocutionary speech acts were identified, consisting of 11 directive speech acts, 24 expressive speech acts, 2 assertive speech acts, 3 commissive speech acts, and 4 declarative speech acts. Expressive speech acts were the most dominant type, indicating that the dialogues in the film are largely used to express emotions, attitudes, and the psychological conditions of the characters. Based on these findings, it can be concluded that the short film “Warga Baru Kampung Pojok” functions not only as a medium of entertainment but also as a representation of social dynamics, cultural values, and communication patterns of Javanese society in an authentic manner through the diverse use of illocutionary speech acts.